(untitled) (Archive of Conferences, 2022)
In this article, the opportunities for the formation of the electricity market in Uzbekistan have been studied and analyzed. The cases of electricity generation capacity, electricity generation capacity, population and geographic location in the Central Asian countries were analyzed. Existing problems in the formation of the electricity market in the region have been investigated, proposals and recommendations for the development of the industry have been developed.